The universalization of the poetry of George Seferis: the significance of English translations. (16th March 2017) - Pose-Fernández, Coralia
Abstract : The English socio-cultural context was crucial to the dissemination of the work of George Seferis in Europe. Early translations appeared in both French and English, but it was the English versions that propelled Seferis toward international recognition and the Nobel Prize, and gave rise to translations into more peripheral literatures such as Spanish. The wide social circle Seferis enjoyed in the English-speaking world was a key factor in his early success in the United Kingdom. Other determinants were British intellectuals' empathy for the Greeks during the Colonels' dictatorship and their liking for modern poetry similar to that of T. S. Eliot.